Accelerated Ice Growth in Rivers - Calkins,Darryl J (1979)
Solid ice growth rates due to the presence of frazil slush beneath the ice cover have been shown to be greater than the so-called static growth. The frazil slush reduces the effective heat of ice solidification and the frazil particles freeze into the interstitial water. Numerical schemes are presented which clearly show the effect of frazil ice porosity on ice cover growth rates and the numerical model using air temperature as the major input is compared with field data on ice thickness in a small river laden with frazil ice beneath its cover. (Author)